Mongol Caucasia - Pubblici, Lorenzo, author.
1 online resource.
Keywords: The work focuses on the Mongol conquest and domination of Caucasia in the 13th century, from the Sea of Azov in the north to present-day Georgia and Armenia. While sedentary civilizations and nomadic cultures had a long history of interaction in this region, the Mongol conquest made it into a frontier in which Medieval Europe and Asia became more intensely integrated and interconnected. The Mongols made Caucasia into a coherent power based on both European and Asian experiences and traditions. The genesis of this deeply transformational process constitutes the central theme of this book.